2009
DOI: 10.1166/jbn.2009.1028
|View full text |Cite
|
Sign up to set email alerts
|

Semisolid Formulation Containing a Nanoencapsulated Sunscreen: Effectiveness, <I>In Vitro</I> Photostability and Immune Response

Abstract: The objective of this work was to verify if hydrophilic gels containing benzophenone-3 loaded nanocapsules (HG-NC BZ3 could improve the sunscreen in vitro effectiveness against UVA radiation and its photostability compared to a conventional hydrogel containing the free sunscreen (HG-BZ3). In parallel, the immune response of the nanostructured system was evaluated by mouse ear swelling test and the local lymph node assay. The nanocapsules were prepared by interfacial deposition of poly(epsilon-caprolactone) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
32
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
4

Relationship

4
6

Authors

Journals

citations
Cited by 56 publications
(36 citation statements)
references
References 18 publications
3
32
0
1
Order By: Relevance
“…Also, an increase in the skin hydration can be observed due to the occlusive properties of the nanoparticles [10]. More advantages include the physical stabilisation of formulations [11] and prevention of drug degradation [12,13] as well as an agreeable sensorial [10].…”
Section: Introductionmentioning
confidence: 99%
“…Also, an increase in the skin hydration can be observed due to the occlusive properties of the nanoparticles [10]. More advantages include the physical stabilisation of formulations [11] and prevention of drug degradation [12,13] as well as an agreeable sensorial [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, its physicochemical characteristics (M¯ w = 228.5 g ؒ mol -1 ; log P: 3.58) favor its permeation through the skin [16] . In a previous study, we reported that the nanoencapsulation of benzophenone-3 improved both its photostability and effectiveness compared to the nonencapsulated sunscreen [17] . Furthermore, some studies showed that polymeric nanocapsules can avoid the favorable permeation and the risk of systemic absorption of lipophilic substances like sunscreens [18,19] .…”
mentioning
confidence: 96%
“…No entanto, a extração do fármaco a partir deste sistema nanoestruturado para fins de quantificação é extremamente difícil, sendo necessária a utilização de uma mistura de solventes que possibilite a solubilização da parede polimérica, bem como do ativo. 10 Assim sendo, o desenvolvimento de um método simples, rápido e preciso para a extração e quantificação do adapaleno a partir das nanocápsulas é altamente desejável. Em vista disso, o presente trabalho teve como objetivo desenvolver e validar um método analítico para quantificação do adapaleno através de cromatografia líquida de alta eficiência (CLAE).…”
Section: Introductionunclassified